Fluid management in major burn injuries - Haberal Mehmet; Abali A. Ebru; Karakayali Hamdi (Indian Journal of Plastic Surgery)
It is a widely accepted fact that severe fluid loss is the greatest problem faced following major burn injuries. Therefore, effective fluid resuscitation is one of the cornerstones of modern burn treatment. The aim of this article is to review the current approaches available for modern trends in fluid management for major burn patients. As these current approaches are based on various experiences all over the world, the knowledge is essential to improve the status of this patient group.